Современите начини на пренесување на македонскиот музички фолклор - Димитријевски, Александар (Асоциация за антропология, етнология и фолклористика »Онгъл«, 2019)
Сè до неодамна, дефиницијата на музичкиот фолклор го вклучуваше „усно-слушното“ пренесување како централна категорија за дистрибуција и восприемање на фолклорните музички артефакти. Ерата на снимени музички материјали произведе дистрибуција на песни и играорна музика на многу поширока публика истовремено елиминирајќи ја потребата од физичко присуство на изведувачите. Дигитализацијата на музичкиот фолклор придонесе за дополнителни консеквенци во музичките, но и во вонмузичките аспекти. Во овој труд, ќе се потрудам да го истражам влијанието на каналите на дистрибуција врз продолжувањето на фолклорната музика во колективната културна меморија преку споредбата на дигиталните наспроти традиционалните начини на пренесување во современо опкружување. Until recently, the definition of music folklore included “oral/aural” as a central category for distribution and reception of folk music artefacts. The recording era facilitated the distribution of the song and dance music to a much wider audience while eliminating the need for physical presence of the performers. The digitization of music folklore has had further consequences both in musical and non-musical aspects. On the other hand, the contemporary presentation of the Macedonian musical folklore started with the radio broadcast in the first half of the 20th century, continued with the television in the second half of the 20th century, and since the beginning of the 21st century mostly transferred on the internet. All of the media and stage performances inevitably included transformed repertoire, and modern appliances for sound amplification and recording which led to preservation and a vast quantity of archived music material. Overall, the elaboration of the researched material explicitly proofed an existence of a large number of musical elements inherited from the traditional forms, but also their transformation, or more likely adaptation in the contemporary environment. Therefore, the contemporary means for transfer of the Macedonian music folklore are in continuity with the tradition, regardless of the significant changes that happened in the regional music culture in the meantime.
The Contemporary Means for Transfer of the Macedonian Music Folklore
ЕДИНАДЕСЕТИ ЦАР-ШИШМАНОВИ ДНИ В САМОКОВ, ТРИДЕСЕТ И СЕДМИ НАУЧНИ ЧЕТЕНИЯ НА АСОЦИАЦИЯ ЗА АНТРОПОЛОГИЯ, ЕТНОЛОГИЯ И ФОЛКЛОРИСТИКА „ОНГЪЛ“, САМОКОВ, 29. СЕПТЕМВРИ – 1. ОКТОМВРИ 2017 Г.
Keywords: Macedonian music folklore; македонски музички фолклор; музички артефакти